Biological findings from a newly developed photo-identification catalog for the critically endangered Rice’s whale (Balaenoptera ricei) - Laura Aichinger Dias; Kevin P. Barry; Lance P. Garrison; Jenny Litz; Lynsey A. Wilcox Talbot; Ruth Y. Ewing; Anthony Martinez (PLoS ONE, 2025)
The Rice’s whale is among the world’s most endangered whales. It has a small population size, low genetic diversity, and is exposed to several anthropogenic threats. In this study, we compiled photographs taken from whale sightings during vessel-based research surveys conducted by the U.S. National Marine Fisheries Service, Southeast Fisheries Science Center between 2004 and 2019 and used photo-ID techniques to develop an identification catalog. Thirty-one whales were individually identified based on dorsal fin attributes and body marks. On the dorsal fin, lacerations, nicks and notches were the most commonly available attributes used for identification and matching. Cookiecutter shark bite scars were widely present on the body of the whales and also served for identification and matching. Of the 31 whales, 28 were sighted multiple times with time between sightings ranging from seven days to more than 15 years. Individual genotyping and sexing were available for 25 cataloged whales. Genotyping confirmed that whales identified via photographs were genetically unique and sexing resulted in 14 females and 11 males. Here we also present insights into rarely recorded presumed mother and calf pairs, with three female whales identified as presumed mothers. Finally, we document dorsal fin disfigurements, body deformities and confirm the identity of a whale mortality. Our study reveals the need for the long-term monitoring of Rice’s whale individuals, especially presumed mothers and calves, and to further investigate potential human threats to this population using photo-identification techniques.